Primeros registros y aportes a la distribución de la avifauna de Santiago del Estero, Argentina - Quiroga, Oscar Bernardo; Capllonch, Patricia; Pérez Bogado, Walter Emanuel; Soria, Karina (Nuestras Aves, 2016)
Este artículo no cuenta con un resumen.